Optimization of Fire Hydrant Maintenance to Minimize Fire Incidents on Board MV. HABCO CARINA - Setiawan, Budi; Widyaningsih, Upik; Amrullah, Romanda Annas; Haryanto, Tri; Sitepu, Firdaus (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Fires on board a ship are an emergency situation that poses a high risk to the safety of the crew, cargo, and the ship itself. Therefore, the readiness and quality of fire extinguishing system maintenance, especially fire hydrants, are crucial aspects in supporting shipping safety. This study aims to analyze the actual condition of fire hydrant maintenance on the MV Habco Carina, identify challenges encountered, and formulate maintenance optimization efforts to ensure the fire extinguishing system functions optimally during emergencies. The study used a qualitative descriptive method through direct observation on board the ship and interviews with the ship's officers and crew. The study was conducted during the researcher's 12-month sea practice on the MV. Habco Carina. The research results show that several fire hydrant components such as hoses, nozzles, valves, and fire pumps are not in optimal condition due to a lack of regular maintenance, minimal technical competence of some crew members, and weak supervision and documentation. This results in low water pressure and suboptimal system function during fire drills. Recommended optimization efforts include improving the quality of scheduled technical maintenance, strengthening the implementation of the PMS, improving crew competence through technical training, and routinely evaluating the effectiveness of the fire hydrant system. With the implementation of more structured and standardized maintenance, the fire hydrant system is expected to support ship preparedness in preventing and handling fires.